"The pitous pite deserveth": Justice, Violence, and Pity in the Prioress's Tale and "The Jew and the Pagan". (3rd April 2022) - Hines, Jessica
ABSTRACT: This article analyzes the role of pity in the construction and management of structures of antisemitism in late fourteenth-century English literature. Reading poet John Gower's "The Jew and the Pagan" from the Confessio Amantis and his close contemporary Geoffrey Chaucer's the Prioress's Tale as in dialogue with one another, I ask how to make sense of the logic of these two tales that espouse pity and mercy and enact violence and cruelty. I argue that in these narratives we can see Gower and Chaucer explore the relationship between pity and violent justice, and, in the process, we can see how the tales enact a strategic essentializing of Jews as unjust, pitiless, and unpitiable to justify antisemitic violence. Study of these two texts together, then, can help both to shed light on the perennial question of authorial intention in the Prioress's Tale and also the importance of pity in studying long histories of antisemitism.